Energy harvesting through the triboelectric nanogenerator (TENG) based on polyurethane/cellulose nanocrystal - Blancas Flores, Jose Miguel; Morales Rivera, Juan; Rocha Ortiz, Gilberto; Hernandez Ahuactzi, Irán Fernandez; Cabrera Chavarria, Jose Jesus; Andrade Melecio, Hugo Armando; Astudillo Sanchez, Pablo Daniel; Antolin Ceron, Victor Hugo (International Journal of Renewable Energy Development, 2024)
This study investigates how physical and mechanical properties affect the performance of triboelectric nanogenerators (TENGs). Polyurethane (PU) was prepared using two methods: (i) one-step PU (non-chain extended polyurethane) and (ii) two-step PU (chain extended polyurethane) via the prepolymer method; both types were filled with different concentrations of nanocrystalline cellulose. Mechanical properties significantly influence the deformation at the material interface that occurs during contact or friction. Key surface characteristics, including surface energy, geometry, and physicochemical properties, affect the effective contact area and potential distribution. One-step PU with 0.1 % CNC demonstrates a maximum capacitance of 29.20 pF, a voltage of 2.04 V, an electric current of 0.43 µA and power of 0.89 µW, representing a 74.5 % increase in power compared to the neat one-step PU, exhibits significant potential for TENG applications. Performance improvements are associated with lower concentrations of cellulose nanocrystals, enhanced hydrogen bonding, and beneficial surface energy. The observed enhancements in output are attributed to improved internal polarization from well-dispersed crystalline nanocellulose, increased crystallinity of the soft segment, and reduced charge transfer mechanisms due to amino groups in the chain extender. However, the impact of the molecular structure and conformation of polyurethanes on triboelectrification remains unclear, highlighting the need for theoretical models and experimental data. This research provides a practical approach for developing stretchable triboelectric materials with enhanced mechanical properties, emphasizing the importance of considering factors such as mechanical parameters, nanofiller content, and surface physicochemical properties to optimize TENG design.